Learning communities in educational partnerships : action research as transformation - Glenn, Máirín (Bloomsbury Academic, 2017)
Learning Communities in Educational Partnerships shows how theory and practice come into lived interplay in social spaces where theory informs practice and practice turns into theory. Drawing on their own experiences of becoming a learning community, the authors introduce the ideas underpinning self-study action research. Through a series of first-hand practitioner accounts, the chapters describe and explain how to engage in processes of inquiry and establish learning communities, how to make space for professional conversations and how to develop living theories from within daily practice. The book shows how meaningful change can take place, both in educational improvements and also in more transformative professional learning, when educators are encouraged to draw on their own personal educational values and share their idea.